2018
DOI: 10.26714/mki.1.2.2018.6-10
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Murottal Therapy in Decreasing Depression of Patients Undergoing Hemodialysis

Abstract: Background: Hemodialysis can be performed 1 to 3 times a week according to the degree of kidney damage and takes 3 - 5 hours each time. The activity done regularly and continuously throughout life and cause negative effects such as discomfort, decreased quality of life including physical health, psychological, spiritual, and socioeconomic status. The psychological impacts include anxiety, stress and depression. This research aimed to analyze the influence of Murottal therapy on depression of patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
3
0
3
Order By: Relevance
“…Mathematics has a role that greatly contributes to science and technology. Mathematics becomes the right tool for problem solving in science (Rahayu & Hidayati, 2018). Although most students have difficulty in understanding complex mathematical concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematics has a role that greatly contributes to science and technology. Mathematics becomes the right tool for problem solving in science (Rahayu & Hidayati, 2018). Although most students have difficulty in understanding complex mathematical concepts.…”
Section: Introductionmentioning
confidence: 99%
“…This awareness will lead to totality surrender to Allah, in this state the brain in alpha waves in the form of brain waves creates optimal brain energy so that it can relieve stress and reduce anxietyn. 18 The results of this study indicate a p-value of 0.007 in group I and 0.001 in group II < (0.05), it can be concluded that there is a significant difference between anxiety levels in patients pre-cardiac catheterization before and after classical music therapy and murottal therapy at RSUP dr. Kariadi Semarang. Classical music therapy and murottal therapy are both sounds that can provide a therapeutic effect by providing relaxation to the patient so as to reduce the anxiety experienced by patients pre cardiac catheterization.…”
Section: Yunie Armiyati / Murottal and Clasical Music Therapy Reducinmentioning
confidence: 62%
“…This sense of calm will then provide a positive emotional response that is very influential in bringing about positive perception. 18 Researchers used Ar-rahman's letter because of the surah contains a great wisdom for humanity in general and for Muslims in particular. This is related to the degree of thankfulness in the broadest sense of the meaning of the disobedience of the giver (Allah Almighty).…”
Section: Yunie Armiyati / Murottal and Clasical Music Therapy Reducinmentioning
confidence: 99%
“…Rasa tenang saat mendengarkan murottal akan memberikan respon emosi positif yang sangat berpengaruh dalam mendatangkan persepsi positif. Riset sebelumnya juga menunjukkan pemberian terapi murottal Al Qur'an mampu menurunkan tingkat stres dan depresi pasien yang menjalani hemodialisis (Rahayu, Hidayati, & Imam, 2018) Temuan penelitian ini juga menguatkan studi sebelumnya tentang "Pengaruh musik dan imagery dalam menginduksi relaksasi dan mengurangi mual dan emesis pada pasien dengan kanker yang sedang menjalani kemoterapi" yang juga menunjukkan hasil positif adanya penurunan signifikan dalam frekuensi mual dan emesis dari waktu ke waktu setelah diberikan musik yang dikombinasikan dengan imagery selama 6 minggu pengobatan. Efek relaksasi mendengarkan musik dan imagery mampu meningkatkan relaksasi dengan menurunkan heart rate dan rasa mual lebih besar dibanding hanya dengan imagery saja (Montserrat Gimeno, 2010).…”
Section: Pembahasanunclassified